Le discours aux morts dans « La guerre de Troie n’aura pas lieu » de Giraudoux - Fraisse, Luc (Studia Romanica Posnaniensia, 2006)
The "Speech to the Dead" delivered by Hector in Jean Giraudoux's play The Trojan War Will Not Take Place (1935) exemplifies a cultural adaptation achieved by moving the relevance of the interwar period into the world of antiquity and the world of Homer. In 1935 Hector's speech expresses the protest of the whole generation against the First World War. But a closer look at this famous scene will demonstrate that Giraudoux actually defines the nature of the theatrical word which enables what is absent from the stage to appear on the stage, and which gets addressed to the unknown, mysterious interlocutors. Therefore the explication of these two tirades unveils a peculiar theory of the theatrical language.